2021
DOI: 10.3389/fonc.2021.613949
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Prediction Model for Colorectal Cancer Based on Nine Autophagy-Related Long Noncoding RNAs

Abstract: IntroductionColorectal cancer (CRC) is the most common gastrointestinal cancer and has a low overall survival rate. Tumor–node–metastasis staging alone is insufficient to predict patient prognosis. Autophagy and long noncoding RNAs play important roles in regulating the biological behavior of CRC. Therefore, establishing an autophagy-related lncRNA (ARlncRNA)-based bioinformatics model is important for predicting survival and facilitating clinical treatment.MethodsCRC data were retrieved from The Cancer Genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Our study identified 29 prognosis-associated, m6A-related lncRNAs based on data from 379 COAD patients, and 12 of them were used to construct the m6A-LPS. NKILA and BOLA3-AS1 have been identified as unfavorable factors for colon cancer (Xu et al, 2021a;Guo et al, 2021;Chen et al, 2022;Qiu et al, 2022), which is consistent with the findings of this study. PCED1B-AS1 was reported to promote the proliferation of COAD by regulating the miR-633/HOXA9 axis, which was proven by in vitro and in vivo experiments (Liu et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Our study identified 29 prognosis-associated, m6A-related lncRNAs based on data from 379 COAD patients, and 12 of them were used to construct the m6A-LPS. NKILA and BOLA3-AS1 have been identified as unfavorable factors for colon cancer (Xu et al, 2021a;Guo et al, 2021;Chen et al, 2022;Qiu et al, 2022), which is consistent with the findings of this study. PCED1B-AS1 was reported to promote the proliferation of COAD by regulating the miR-633/HOXA9 axis, which was proven by in vitro and in vivo experiments (Liu et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…According to previous literature, [23][24] combined with the relationship between six HALs and GBM prognosis, as well as the results of GSEA analysis, we speculate that LINC00957 is a lncRNA with research potential, and may have a close relationship with the tumor immune microenvironment…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…S1A-K), and LINC00957 was also confirmed by bioinformatics analysis to be associated with the prognosis of colon cancer. 23 Next for LINC00957, we further explored its role in pancancer. Considering the small number of normal samples for TCGA, we integrated the data from normal tissues in the GTEx database and the data from TCGA tumor tissues and analyzed 34 cancer species and found that significant upregulation was observed in PAAD (p ¼ 1.2e-11), LAML (p ¼ 6.2e-3), PCPG (p ¼ 5.2e-3), KICH (p ¼ 1.9e-25), and CHOL (p ¼ 1.7e-5), and significant downregulation was observed in GBM (p ¼ The tumor mutation landscape was demonstrated to be associated with antitumor immunity.…”
Section: Expression and Prognosis Of Linc00957 In Pan-cancermentioning
confidence: 99%
“…We used Lasso regression analysis and Cox risk regression analysis to identify five CRLs (AC005332.6, AC090114.2, LINC00857, LINC02041, and AL117382.1) that were shown to be independent prognostic variables for PAAD and correctly classified PAAD patients into two separate prognosis categories. Evidence suggests that AC005332.6, AC090114.2, and LINC02041 may serve as prognostic markers for many cancers, including pancreatic cancer [ 42 , 53 , 54 , 55 , 56 ]. Through a ceRNA-mediated mechanism, LINC00857 promotes the growth and invasion of pancreatic cancer cells [ 51 ].…”
Section: Discussionmentioning
confidence: 99%